Situation Report: Hungary, 9 June 1982 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. East German Party and Government Delegation Visits Hungary Polish "Reform" Seen from Budapest The Features of the Principal Forms of Enterprise Further Changes to Regulations Covering Private Retail Trade Agricultural Cooperatives Form a New Type of Enterprise with Private Participation